INNOVATIVE AI-BASED MATHEMATICS LEARNING: A PHILOSOPHICAL PERSPECTIVE OF PRAGMATISM - Siti Julaeha; Maria Edistianda Eka Saputri; Henny Suharyati (Cakrawala Pedagogik, 2026)
The Industrial Revolution 4.0 era has transformed the way humans work, constantly integrating technology. Therefore, mathematics learning needs to be more innovative, contextual, and meaningful to meet the challenges of technological development and social change. The use of Artificial Intelligence (AI) in mathematics learning is considered innovative learning. The implementation of AI-based learning innovations appears to increase the effectiveness, efficiency, and engagement of students in mathematics learning, but not all of them are grounded in philosophical understanding. This article aims to examine innovative AI-based mathematics learning from a pragmatist philosophical perspective, in order to provide a more meaningful, reflective, and contextual conceptual foundation. This study uses a qualitative method with a library research approach, through a critical review of books, journal articles, and relevant scientific publications from the past five years obtained from academic databases such as Google Scholar, Scopus, and ScienceDirect. Data analysis was conducted through the interpretation of texts and discourses and a review of empirical facts to identify patterns, trends, and research gaps related to AI in mathematics learning. The results of the study indicate that although AI is effective in supporting procedural practice and learning engagement, there are conceptual gaps in strengthening the pedagogical foundation, reflective dimensions, and value orientation of learning. Through a pragmatist framework, AI is repositioned not as an epistemic authority but rather as a pedagogical partner that enriches the mathematical learning experience through inquiry, reflection, and meaningfulness in real-world contexts. The study's conclusions emphasize that the success of AI integration in mathematics learning in the Society 5.0 era is determined not only by technological sophistication but primarily by the alignment between pedagogical design, value orientation, and humanistic, democratic, and equitable educational goals.